2010
DOI: 10.1111/j.1365-2265.2009.03634.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperthyrotropinemia: population characteristics, diagnosis, management and outcome after cessation of therapy

Abstract: We recommend obtaining thyroid imaging to distinguish between the two forms of HT. Adherence to recommended doses of thyroxine and probably early cessation of therapy in transient HT can prevent iatrogenic hyperthyroidism in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…In a multicenter retrospective study, we observed a high prevalence of prematurity (21%), small size for gestational age (SGA) (7%), or both (14%) among neonates identified with HT (1). This observation corroborates a previous report by Kohler et al (2) who also found a high prevalence of prematurity in a cohort of newborns with transient congenital hypothyroidism (CH) (38%) and transient congenital HT (18%).…”
Section: Introductionsupporting
confidence: 80%
“…In a multicenter retrospective study, we observed a high prevalence of prematurity (21%), small size for gestational age (SGA) (7%), or both (14%) among neonates identified with HT (1). This observation corroborates a previous report by Kohler et al (2) who also found a high prevalence of prematurity in a cohort of newborns with transient congenital hypothyroidism (CH) (38%) and transient congenital HT (18%).…”
Section: Introductionsupporting
confidence: 80%
“…Although the evolution over time of the cases with eutopic gland is difficult to be predicted preliminarily, in the last few years a lot of studies [6,7,8,9,10,11,12] have been conducted with the purpose of determining how best to discriminate between cases with either T or permanent (P) CH before the age of 3 years, which is currently adopted for reevaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that these two distinct thyroid dysfunctions including CH and persistent HT have a different clinical course. Previous reports also suggests the possibility that HTT might be caused by clinical conditions associated with the preterm birth rather than the abnormality of the thyroid gland itself and therefore infants with persistent HTT showed a higher incidence of transient hypothyroidism after re-evaluation [19][20][21].…”
Section: Discussionmentioning
confidence: 99%